2021
DOI: 10.1051/shsconf/20219401006
|View full text |Cite
|
Sign up to set email alerts
|

Sustainable development in the Russian regions

Abstract: The implementation of the goals, recorded in The 2030 Agenda for Sustainable Development, requires a coordinated solution of problems both at the national level and at the level of single territorial units. The article provides a comparative analysis of individual indicators of the constituent entities of the Russian Federation, compared with the goals of sustainable development. Significant differences are found in achieving sustainable development goals in different regions, the most problematic are the goal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…However, too high differentiation degree can also lead to negative economic results. In this regard, we note the work [12], which shows that most regions are more or less behind the average Russian level for a number of indicators of goal achievement. Therefore, more attention needs to be paid to the regional aspects of the goals and related indicators.…”
Section: Introductionmentioning
confidence: 76%
“…However, too high differentiation degree can also lead to negative economic results. In this regard, we note the work [12], which shows that most regions are more or less behind the average Russian level for a number of indicators of goal achievement. Therefore, more attention needs to be paid to the regional aspects of the goals and related indicators.…”
Section: Introductionmentioning
confidence: 76%
“…The study of transportation systems of the Northern regions of Russia shows that only three regions of these (Nenets Autonomous District, Chukotka Autonomous District, the Republic of Sakha (Yakutia) have less than 30 % of hard-surface capital roads in the structure of lines of communication, most of the transport lines there are seasonal (waterways, winter roads), which have no alternative and therefore are yearly renewable (Figure 1). After analysing the main approaches to the analysis and assessment of transportation systems, which are employed, for example, in interregional differentiation [16][17][18], it was revealed that recent studies of domestic and foreign scientists and practitioners in the field of regional economics and transportation systems management disregard the features of the transportation system available in the regions of the North -the widespread use of temporary vehicle roads (winter roads). They are usually not considered in the case studies of transport availability, transport accessibility and transport opportunities of territories [19][20].…”
Section: Methodsmentioning
confidence: 99%
“…To achieve sustainable development of the region requires integrated work of all spheres of life of the population, aimed at solving the most important problems at the regional level, improving the quality of life of residents inhabiting the territory of the region by achieving a balance between economic, social and environmental development [7][8][9].…”
Section: Introductionmentioning
confidence: 99%